QIṢṢAH AL-QUR'ĀN BAINA AL-TĀRĪKH WA AL-USṬHŪRAH - NUR AKHDA SABILA SUSANTO (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2019)
The debate about the authenticity of the stories in the Qur'an until this century is still the topic of a lively discussion. Especially Orientalists who study Islam with the aim of overthrowing it will make this topic the main debate in their efforts. Departing from many debates and profound assumptions within and outside the Muslim community about the stories in the Qur'an, this paper aims to discuss the stories in the Qur'an whether it is a historical fact or a myth. The method used in the discussion of this paper uses descriptive method to be able to define and discuss narratives that discuss the stories in the Qur'an based on the foundation of the science of interpretation so that results are in accordance with the truth in the Qur'an itself. And it can be concluded that historical stories or scientific stories that occur in the Qur'an that occur or which do not occur are a sign, or a symbol of the verse to be considered by all Muslims, because there is wisdom as guidance and guidance for the lives of Muslims.